How to put forest and conservation genomics into motion for and with Indigenous communities? - Lyne Touchette; Jean-Michel Beaudoin; Nathalie Isabel; Nancy Gélinas; Ilga Porth (The Forestry Chronicle, 2021)
Sustainable management and conservation (SMC) projects for natural resources in collaboration with Indigenous Peoples using a genomics approach are increasing in number. Information and tools/applications derived from genomics can be useful to them, particularly in the context of climate change. However, the challenge of translating these applications into practice and harnessing them to serve Indigenous communities remains. We present an exploratory literature review that addresses: (1) the demonstrated utility of genomics in SMC projects involving Indigenous Peoples, (2) some issues that may limit the adoption of genomics tools, and (3) the collaborative work between researchers and Indigenous communities in the analyzed studies. The demonstrated uses identified were largely of a socioecological nature. The complementary nature of Indigenous knowledge and scientific knowledge in genomics was recognized as an opportunity that should be further developed to address current challenges such as climate change. Regarding the adoption into practice of this technology in SMC projects, in addition to similar issues with other end users, the integration of the needs, traditional values and knowledge of Indigenous communities in genomics projects also represents a challenge in the context of the decolonization of genomics research. Finally, community-researcher collaboration was identified as a key element in promoting the successful uptake of genomics in SMC.